Social Economic Perspectives of Homecoming Tradition: An Indonesian Context - Oktavio, Adrie; Indrianto, Agoes Tinus Lis (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2019)
Homecoming has been practiced by most Indonesians as a routine tradition that cherished every year. This interesting practice has developed rapidly as an impact of the integration of capitalist economic systems in the early 1970s. The tradition of homecoming in Indonesia mostly occurs at the moment of religious holidays. This phenomenon is considered an essential part of the celebration. As the largest Moslem population in the world, the most prominent homecoming activity in Indonesia mostly happens during Eid Mubarak Celebration. At this moment, not only Moslem but almost all the people in the country go back to their hometown. Every year, this tradition is getting bigger in numbers and giving more significant impacts on the country in terms of social and economics. Therefore, this study tries to describe the homecoming tradition for Indonesia, specifically seen from a socio-economic perspective. As a qualitative content analysis study, this study analyses related works of literature, documentation, and publications relevant to the topic. The result is written descriptively by explaining the phenomena, discussing the impacts and proposing solutions. The results show that going home is proven to provide a substantial multiplier effect on the socio-economic side. From social perspectives, homecoming means the fulfillment of primordial and emotional interests to strengthen the relationship between family and friends. On the other hand, this tradition also boosts the economic development of the regions, which is interpreted as equalization or circulation of money from urban to rural areas in the country. Keywords: homecoming, tradition; impacts, social and economics